Improving the value of ultrasound in children with suspected appendicitis: a prospective study integrating secondary sonographic signs - Reddan, Tristan (Ultrasonography, 2019)
PURPOSE: The purpose of this study was to determine whether the awareness and inclusion of secondary sonographic signs of appendicitis, in combination with a structured evaluation as part of engagement and training for sonographers, improved appendix visualization rates and reduced equivocal findings in children with suspected acute appendicitis. METHODS: This was a prospective study of 230 children at a tertiary children’s hospital in Australia referred for an ultrasound examination of suspected appendicitis. The ultrasound findings, radiology reports, histology, clinical results, and follow-up were collated. Secondary signs were used as an additional assessment of the likelihood of disease where possible, even in the absence of an identified appendix. RESULTS: The implementation of a structured evaluation as part of sonographer engagement and training resulted in a 28% improvement in appendix visualization (68.7%) compared with a prior retrospective study in a similar population (40.7%). The diagnostic accuracy was 91.7%, with likelihood ratios suggesting a meaningful influence of the pre-test probability of appendicitis in children studied (positive likelihood ratio, 11.22; negative likelihood ratio, 0.09.). Only 7.8% of the findings were equivocal. A binary 6-mm diameter cut-off did not account for equivocal cases, particularly lymphoid hyperplasia. CONCLUSION: Engagement of sonographers performing pediatric appendiceal ultrasound through training in the scanning technique and awareness of secondary signs significantly improved the visualization rate and provided more meaningful findings to referrers.